Corporate social performance, analyst stock recommendations, and firm future returns. (3rd February 2014) - Luo, Xueming; Wang, Heli; Raithel, Sascha; Zheng, Qinqin
<x xml:space="preserve">Abstract</x> This study posits that security analysts heed corporate social performance information and factor it into their recommendations to general investors. In particular, as corporate social performance is often uncertain and ambiguous to general investors, analysts may serve as the informational pathway connecting corporate social performance to firm stock returns. Thus, we argue that analyst recommendations mediate the relationship between corporate social performance and firm stock returns. On the basis of not only a qualitative study with literature searches and interviews of stock analysts but also a quantitative study with two longitudinal samples of large firms, we find support for these arguments. Our findings uncover an information‐based underlying mechanism for the link between corporate social performance and financial performance. Copyright © 2013 John Wiley & Sons, Ltd.